Practical Access to Aromatic Thiocyanates by CuCN‐Mediated Direct Aerobic Oxidative Cyanation of Thiophenols and Diaryl Disulfides1. Issue 35 (5th November 2014) - Castanheiro, Thomas; Gulea, Mihaela; Donnard, Morgan; Suffert, Jean
Abstract: The practical and mild aerobic oxidative CuCN‐mediated cyanation of thiophenols and diaryl disulfides was investigated. The reaction was performed in air at room temperature and reached aromatic thiocyanates in moderate to good yields starting from a broad range of diversely functionalized substrates. Abstract : A practical and mild aerobic oxidative CuCN‐mediated cyanation of thiophenols and diaryl disulfides is reported. The reaction is performed in air at room temperature and reaches aromatic thiocyanates in moderate to good yields starting from a broad range of diversely functionalized substrates. TMEDA = N, N, N′, N′ ‐tetramethyl‐1, 2‐ethylenediamine.